Transcriptomics and metabolomics provide insight into the anti-browning mechanism of selenium in freshly cut apples - Wang, Xinyue; Zhang, Xuemei; Jia, Peng; Luan, Haoan; Qi, Guohui; Li, Han; Guo, Suping (Frontiers in Plant Science, 2023)
Enzymatic browning has a considerable negative impact on the acceptability and marketability of freshly cut apples. However, the molecular mechanism by which selenium (Se) positively affects freshly cut apples in this regard is not yet clear. In this study, 0.75 kg/plant of Se-enriched organic fertilizer was applied to 'Fuji' apple trees during the young fruit stage (M5, May 25th), the early fruit enlargement stage (M6, June 25th), and the fruit enlargement stage (M7, July 25th), respectively. The same amount of Se-free organic fertilizer was applied as a control. Herein, the regulatory mechanism by which exogenous Se exerts its anti-browning effect in freshly cut apples was investigated. The results showed that the M7 treatment applied in Se-reinforced apples could remarkably inhibit their browning at 1 h after being freshly cut. Additionally, the expression of polyphenol oxidase (PPO) and peroxidase (POD) genes treated with exogenous Se were significantly reduced compared to controls. Moreover, the lipoxygenase (LOX) and phospholipase D (PLD) genes, which are involved in membrane lipid oxidation, were expressed at higher levels in the control. The gene expression levels of the antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), glutathione S-transferase (GST), and ascorbate peroxidase (APX) were upregulated in the different exogenous Se treatment groups. Similarly, the main metabolites measured during the browning process were phenols and lipids; thus, it could be speculated that the mechanism by which exogenous Se produces its anti-browning effect may be by reducing phenolase activity, improving the antioxidant capacity of the fruits, and alleviating membrane lipid peroxidation. In summary, this study provides evidence and insight regarding the response mechanism employed by exogenous Se to inhibit browning in freshly cut apples.